(untitled) - Quinn, James Brian (Homewood, Ill., 1980)
Planning activities in such enterprises often become bureaucratized, rigid, and costly paper-shuffling excercises divorced from actual decision processes.
Keywords: Kế hoạch kinh doanh,Business planning